New insights from a high-resolution look at gastrulation in the sea urchin, Lytechinus variegatus. (December 2017) - Martik, Megan L.; McClay, David R.
Abstract: Background: Gastrulation is a complex orchestration of movements by cells that are specified early in development. Until now, classical convergent extension was considered to be the main contributor to sea urchin archenteron extension, and the relative contributions of cell divisions were unknown. Active migration of cells along the axis of extension was also not considered as a major factor in invagination. Results: Cell transplantations plus live imaging were used to examine endoderm cell morphogenesis during gastrulation at high-resolution in the optically clear sea urchin embryo. The invagination sequence was imaged throughout gastrulation. One of the eight macromeres was replaced by a fluorescently labeled macromere at the 32 cell stage. At gastrulation those patches of fluorescent endoderm cell progeny initially about 4 cells wide, released a column of cells about 2 cells wide early in gastrulation and then often this column narrowed to one cell wide by the end of archenteron lengthening. The primary movement of the column of cells was in the direction of elongation of the archenteron with the narrowing (convergence) occurring as one of the two cells moved ahead of its neighbor. As the column narrowed, the labeled endoderm cells generally remained as a contiguous population of cells, rarely separated by intrusion of a lateral unlabeled cell. This longitudinal cell migration mechanism was assessed quantitatively and accounted for almost 90% of the elongation process. Much of the extension was the contribution of Veg2 endoderm with a minor contribution late in gastrulation by Veg1 endoderm cells. We also analyzed the contribution of cell divisions to elongation. Endoderm cells in Lytechinus variagatus were determined to go through approximately one cell doubling during gastrulation. That doubling occurs without a net increase in cell mass, but the question remained as to whether oriented divisions might contribute to archenteron elongation. We learned that indeed there was a biased orientation of cell divisions along the plane of archenteron elongation, but when the impact of that bias was analyzed quantitatively, it contributed a maximum 15% to the total elongation of the gut. Conclusions: The major driver of archenteron elongation in the sea urchin, Lytechinus variagatus, is directed movement of Veg2 endoderm cells as a narrowing column along the plane of elongation. The narrowing occurs as cells in the column converge as they migrate, so that the combination of migration and the angular convergence provide the major component of the lengthening. A minor contributor to elongation is oriented cell divisions that contribute to the lengthening but no more than about 15%. Highlights: Sea urchin gastrulation occurs with minimal lateral convergence and a predominance of extension of clones of cells. Cell divisions during gastrulation approximately double the number of cells in the gut. Up to 15% of the total length of the gut is due to divisions biased along the plane of elongation.